2009
DOI: 10.1371/journal.pone.0006717
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Molecular Basis of Individual Differences in Human Umami Taste Perception

Abstract: Umami taste (corresponds to savory in English) is elicited by L-glutamate, typically as its Na salt (monosodium glutamate: MSG), and is one of five basic taste qualities that plays a key role in intake of amino acids. A particular property of umami is the synergistic potentiation of glutamate by purine nucleotide monophosphates (IMP, GMP). A heterodimer of a G protein coupled receptor, TAS1R1 and TAS1R3, is proposed to function as its receptor. However, little is known about genetic variation of TAS1R1 and TAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 30 publications
6
79
1
13
Order By: Relevance
“…34 Lugaz et al 119 showed that, like bitter taste, there seems to be a spectrum of ability to taste monosodium L-glutamate, with thresholds differing approximately five-fold between tasters and hypotasters. Shigemura et al 120 identified two SNPs that conferred variation in taste recognition threshold: TASR1-372 and TAS1R3-757 haplotypes. The TASR1 A372T SNP confers increased sensitivity to umami, while the TAS1R3 R757C SNP results in a higher threshold for detection.…”
Section: Genetic Chemosensory Variationmentioning
confidence: 99%
“…34 Lugaz et al 119 showed that, like bitter taste, there seems to be a spectrum of ability to taste monosodium L-glutamate, with thresholds differing approximately five-fold between tasters and hypotasters. Shigemura et al 120 identified two SNPs that conferred variation in taste recognition threshold: TASR1-372 and TAS1R3-757 haplotypes. The TASR1 A372T SNP confers increased sensitivity to umami, while the TAS1R3 R757C SNP results in a higher threshold for detection.…”
Section: Genetic Chemosensory Variationmentioning
confidence: 99%
“…Some people are specifically insensitive to MSG, 97 which is partly caused by alleles of the umami receptor. 98-100 The detection of a genotype/phenotype relationship implies that the trait is at least partially heritable, but we know of no published twin or family studies that estimate the contribution of genes to trait variation.…”
Section: Umami: Savory or Meatymentioning
confidence: 99%
“…Taking a ham and cheese sandwich as an example (Fig. 1), we might imagine that people with sensitive alleles might differentially detect the mild sweetness of onion (TAS1R3), 89 the savory glutamate taste of tomato (TAS1R3), 98,100,170 the bitterness of watercress (TAS2R38), 50 the smell of cheese (OR11H7), 154 or the boar taint odor of ham (OR7D4). 153 We envision that a combination of allelic differences might contribute to the range of liking for this sandwich.…”
Section: Taste Genetics and Food Intakementioning
confidence: 99%
“…The taste word 'umami' connotes the quality best exemplified by monosodium glutamate. Some people cannot taste umami [65,66], perhaps due in part to genetic variants within its receptor, TAS1R1 (taste receptor type 1 member 1), a heterodimer composed of T1R1 and T1R3, two proteins of the TAS1R family (Table 1) [18,[67][68][69][70][71]. In addition to this receptor, glutamate may also be sensed by receptors similar to those that recognize glutamate in the brain [72].…”
Section: Differences In Umami Sour and Salty Taste Detectionmentioning
confidence: 99%